Clindamycin removal from aqueous solution by non-thermal air plasma treatment: performance, degradation pathway and ensuing antimicrobial activity. (11th October 2022) - Akbarzadeh, Abbas; Ghomi, Hamid Reza; Rafiee, Mohammad; Hosseini, Omid; Jahangiri-rad, Mahsa
Abstract: The present study set out to investigate clindamycin (CLN) removal from aqueous solution using non-thermal plasma (NTP) under atmospheric air conditions and to address the effects of some variables including pH, initial concentration of CLN, and working voltage on CLN degradation. The result showed that the NTP system exhibited excellent degradation rate and mineralization efficiency on CLN in 15 min under neutral conditions, which exceeded 90 and 45%, respectively, demonstrating its conversion to other organic by-products. Furthermore, CLN degradation was largely dependent upon the initial pH of solution, applied voltage, and reaction time. Specifically, under acidic conditions (pH = 3), working voltage of 24 kV and after 15 min of reaction, almost 100% of CLN was degraded. NTP-initiated CLN degradation products through LC-MS/MS analysis, determined within 10 min of reaction, inferred that the complex structure of CLN has undergone deterioration by active radical species which subsequently generated small molecular organic compounds. Chemical processes involved in CLN degradation were found to be demethylation, desulfonylation, dechlorination, hydroxylation and deamination. Lastly, antimicrobial susceptibility tests revealed that the activity of CLN was reduced following NTP treatment, which is also in good agreement with the minimum inhibitory concentration (MIC) values obtained from microdilution analyses. HIGHLIGHTS: Clindamycin degradation by non-thermal plasma was investigated. Almost 90% removal of CLN was achieved within 15 min of reaction. pH, initial CLN concentration and working voltage were the key factors influencing CLN removal. Intermediate products and possible CLN degradation pathway were proposed. Graphical Abstract